The legal status of journalist оn media rights system (Herald of Journalism, 2018)
This research evaluates the legal status of the rights of journalists on the media system.The author in the article shows the features of the creative work of the journalist and the realization of professional special interests in the status of the journalist, which derived from the specificity of its social role. The article also discusses the most important properties which together distinguish journalism from other professions, and above all aboutits artistic character and the public service elements. The article also provides an overview on the recently published study about the legal status of the rights of journalists on the media system.Key words: mass media, journalist, regulation, law, rights, legal status.